Smart cities - Gitlin, Marty (21st century skills innovation library. Exploring the internet of things., 2021)
Investigates the history, creation, and operation of smart technology used in cities. Highlights smart traffic signals, automatic street lights, sensors that detect gunshots, and smart trash cans. Includes a glossary, photographs, and resources for further investigation.